IDENTIFICATION OF BACTERIA CAUSING DIARRHEA IN UNDER-FIVES CHILDREN USING CULTURE METHODS IN BIMA, INDONESIA - Muziburrahman Muziburrahman; Dominicus Husada; Budi Utomo (Universitas Airlangga, 2022)
Background: Diarrhea is still a world health issue which is one of the leading causes of morbidity and mortality, with a mortality rate of close to more than 1.30 million deaths globally in 2015. The prevalence period of diarrhea in Indonesia for under-five children in 2018 is 12.30%. The West Nusa Tenggara province is third of the ranks based on doctor’s diagnosis (13.45%) and clinical symptoms (15.12%). Purpose: This study aims to identify the bacterial infection that causes diarrhea among under-five children in Bima District, West Nusa Tenggara Province. Methods: The cross-sectional study was conducted on under-five children brought to Bolo and Wawo’s Public Health Center with diarrhea and diagnosed with acute gastroenteritis. Results: The samples involved in this study were 102 samples and the results obtained were 1 to 2 types of bacteria in 1 sample. The order of bacteria from the most is E. Coli (29.53%), Klebsiella, sp (25,50%), Shigella, sp (18,79%), Staphylococcus aureus (16,78%), Salmonella Thypii (8,73%), Proteus, sp (0,67%), male (61.76%) had more diarrhea than female (38.24%), with an age range of 1-3 years (53.92%), 0-1 years (37.26%), and 3 until <5 years (8.82%). Conclusion: In this research, it was proven that E. coli bacteria are the leading cause of diarrhea in under-five children.